The Influence of Serawai Melayunese Dialect Towards Students’ English Pronunciation - Mulya, Debby; Mujiyanto, Januarius (English Education Journal, 2018)
During the process of L2 acquisition, most of the students usually face some difficulties in pronunciation. One influential factor that triggers this problem is L1 transfer. Therefore, the objectives of this study were to explain the influence of Serawai Melayunese dialect towards students’ pronunciation of English vowels, consonants, diphthongs, clusters, and words stress syllables and to explain the role of teacher in the development of student’s pronunciation. This research employed qualitative descriptive research. The subjects of this study were 38 students of SMAN 1 South Bengkulu. The data were collected by using questionnaires, student’s recording, observation checklist, and an interview. The results of this study showed that Serawai Melayunese dialect did not strongly give positive transfer on students’ pronunciation of English vowels [ʊ],[ɒ],[ʌ],[ə],[e], consonants [p], [b], [t], [d], [f], [ʃ], [k], [h], [s], [m], [n], [l], [r], and diphthong [ɔɪ]. Moreover, Serawai Melayunese dialect did not strongly give negative transfer on the substitutions of long vowel sounds [i:], [ɒ], [u:], [ɜ:] and [ae] into short vowel sounds [ʊ],[ɒ],[ʌ],[ə],[e], consonant sounds [ph], [th], [kh], [ծ], [dʒ], [ʒ], [tʃ], [ɵ], and [v] into sounds [p], [k], [d], [j], [z], [t], [f]. It occurred not only because of these sounds did not exist in the Serawai Melayunese dialect sound system, but it was also influenced by spelling interference from L1 and lack of pronunciation training. Furthermore, diphthong [aʊ] and two syllable word stress on final position were strongly influenced by Serawai Melayunese dialect. Since this diphthong existed in Serawai Melayunese dialect and stress placement in two syllable words were frequently produced on final position, it influenced positively the student’s English pronunciation. In contrary, Serawai Melayunese dialect did not give negative transfer on students’ pronunciation of diphthongs [eɪ], [aɪ] [ʊe], [eə], and [ʊə]. The students pronounced these diphthongs improperly were caused by spelling interference from L1 and lack of pronunciation training. In addition, Serawai Melayunese dialect did not give positive and negative transfer of English consonant clusters [str] and [st] since they were able to recognize those words or teacher gave pronunciation training. Last, teacher’s awareness about the importance of teaching pronunciation was still inadequate. Pronunciation instruction was least granted attention by the teacher. As results, teacher was reluctant to monitor and to correct students’ pronunciation.